El encuentro intersubjetivo y sus mediaciones en la fenomenología hermenéutica de Paul Ricoeur - Grassi, Martín (ARFIL y UNL, 2018)
The present work pretends to be an introduction to the problem of intersubjectivity from the phenomenological and hermeneutical point of view of Paul Ricoeur. The phenomenon of intersubjectivity will be studied from a gnoseological, ethical, sociological and hermeneutical perspective, trying to disclose how a mutual acknowledgment between strange subjects in a common world can be possible. Meditation upon intersubjectivity must always attend on the irreductibility of persona as such, acknowledgment made possible by love and charity, and that reveals it sense in the espirit of giveness. In the other hand, the irreducitibility of persona implies rejecting the possibility of building a third substance, different from the I and the Thou, and which would submit them to its reality, as structuralism and hegelianism seems to propose. We intend to show that Ricoeur’s position is one of a genetic phenomenology that search for the strange from the own, stating the homo capax that acts always in a shared world (Lebenswelt) as its central idea.